Comedy writing as method: reflections on screenwriting in creative practice research. Issue 3 (3rd July 2019) - Batty, Craig; Taylor, Stayci
ABSTRACT: Comedy writers use their practice to raise questions and create awareness about social, political and cultural issues, but can these practitioners be considered academics? With creative modalities of enquiry now commonplace in universities – where research is used to shape one's practice, resulting in creative work that embodies that research – when does comedy writing start to take on a different function? In this article, we discuss comedy screenwriting in an academic setting, arguing that it has potential as a rigorous mode of research that can sit happily alongside art, design, creative writing and media practice. Much has been written about creative practice research, yet not so much has been written about the form this type of research takes; specifically, why one might choose comedy to express, embody or otherwise perform the findings of research. Here, then, we draw on our experiences of undertaking screenwriting projects using comedy to discuss the ways in which researchers might use the comic mode to present their findings in imaginative, innovative and fun ways that can expand understanding and, potentially, garner impact.